If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4z + 6 = 3z + -10 Reorder the terms: 6 + 4z = 3z + -10 Reorder the terms: 6 + 4z = -10 + 3z Solving 6 + 4z = -10 + 3z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-3z' to each side of the equation. 6 + 4z + -3z = -10 + 3z + -3z Combine like terms: 4z + -3z = 1z 6 + 1z = -10 + 3z + -3z Combine like terms: 3z + -3z = 0 6 + 1z = -10 + 0 6 + 1z = -10 Add '-6' to each side of the equation. 6 + -6 + 1z = -10 + -6 Combine like terms: 6 + -6 = 0 0 + 1z = -10 + -6 1z = -10 + -6 Combine like terms: -10 + -6 = -16 1z = -16 Divide each side by '1'. z = -16 Simplifying z = -16
| (-1/4y)-1=23.75 | | 5f=2f+6 | | 4x^2+x+50=0 | | 12+-7t=30 | | (4-3d)=5(2d+2) | | 1x+6(y+2x)=0 | | 12-7t=30 | | 6x-4c=12b | | 12a+3=30 | | 6x+3=x+2a | | h=-16t^2+96t+40 | | (5x-9)(8x+3)=0 | | (9z+1)+(10z-6)+90=180 | | -3-(-15)/3 | | 49+29m=25+37m | | 2m^-3n^0/(2m^-4n^2)^3 | | 8.2x^2+1341x=40000 | | 7(x+2)-1=48 | | -5x/7+16=4 | | n-4-27=38 | | 5-0*3+9/3= | | 8(2x-7)= | | 0=-16t^2+30t+78 | | t=947*5+17086 | | y=-4sin(4x)+2 | | 21947=974x+17086 | | t=974x+17086 | | 2p^2-17p+8=0 | | 4b^2+2b-42=0 | | 3x+18z=90 | | -8.75z+12.5=12.5 | | 3y+0.4=-0.2 |